Toward an integrative model of SME performance in Nigeria - Aminu, Mohammed Ibrahim; Mahmood, Rosli (2015)
Nigerian government had been spending an enormous amount of money for the entrepreneurial and small business development programs in order to develop a vibrant SME sector.Nevertheless, most of these programs lasted with poor results generally. This led to the implementation of national policy on micro, small and medium enterprises, which identifies lack of application of knowledge and entrepreneurial attitude by SMEs as the principal reasons for their nonperformance tradition.Although, this policy brings about unprecedented improvements in the sector, still it is contributing less compared to other developing countries.This is because, in the present rapid changing environment, the strategy of accumulating such intangible resources is not enough to determine significant performance. Consequently, this paper draws upon the resource-based, knowledge-based, and dynamic capabilities perspectives to initiate a move toward the development of an integrative model of SME performance in the Nigerian turbulent environment.